Implementasi Tanggungjawab Pemerintah Daerah Dalam Penanggulangan Penyakit HIV/AIDS di Daerah Kabupaten Lombok Timur - Putra, Guruh Sirgantera (CV. Ridwan Publisher, 2019)
Communicable diseases that become long-term national development priorities 2005-2025 is malaria, dengue fever, diarrhea, polio, filaria, leprosy, pulmonary tuberculosis, HIV/AIDS, pneumonia, and other diseases that can be prevented by immunization. Although infectious diseases are a priority target of the prevention and eradication of the Millennium Development Goals (Millennium Development Goals) is the dengue hemorrhagic fever ( DHF ), malaria and tuberculosis, but in the area of East Lombok district HIV / AIDS is also urged to be eradicated, as has been become a plague that claimed the lives of hundreds of people every year. This study aims to determine how the spread of HIV/AIDS and the efforts of local authorities in tackling HIV/AIDS. The method used is a qualitative, descriptive analysis method, in checking the validity and reliability of the data used triangulation of researchers. Implementation Responsibility of Local Government in tackling infectious diseases HIV/AIDS in East Lombok district can not fully support the achievement of health development goals, namely realize the degree of public health as high, as a result there are still many obstacles that could potentially hinder efforts to control infectious diseases HIV/AIDS. Theoretic approach in the prevention of infectious diseases HIV/AIDS ternayata should be supported by lawmakers thoughtful, orderly and dignified, and behave as a